2021
DOI: 10.1007/s00296-020-04776-1
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to best practice consensus guidelines for familial Mediterranean fever: a modified Delphi study among paediatric rheumatologists in Turkey

Abstract: Background Although not validated fully, recommendations are present for diagnosis, screening and treatment modalities of patients with familial Mediterranean fever (FMF). Objective To review the current practices of clinicians regarding FMF and reveal their adherence to consensus guidelines. Methods Fifteen key points selected regarding the diagnosis and management of FMF were assessed by 14 paediatric rheumatologists with a three-round modified Delphi panel. Results Consensus was reached on the following asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In the studies conducted with canakinumab, no side effects were observed other than mild infection, the drug was reported to be safe, and no severe side effects were observed in our study [ 36 38 ]. No serious adverse events were observed in the present study, and patients with SARS-CoV2 infection were treated without hospitalization.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the studies conducted with canakinumab, no side effects were observed other than mild infection, the drug was reported to be safe, and no severe side effects were observed in our study [ 36 38 ]. No serious adverse events were observed in the present study, and patients with SARS-CoV2 infection were treated without hospitalization.…”
Section: Discussionsupporting
confidence: 54%
“…There are limited data on the drug’s dose intervals and discontinuation in the adult patient group. If no attacks and subclinical inflammation are observed after starting canakinumab, dose intervals can be doubled initially and then tripled if no new attack occurs within one year [ 38 ]. As the present study is a real-life study, which included a limited number of cases and is conducted in routine outpatient clinic conditions, it may contribute to the literature in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of colchicine‐resistant patients in this study was 19.5%. Previous studies have reported that approximately 5%–10% of FMF patients were not responsive to colchicine 10,15,22 . Long‐term administration of colchicine in pediatric FMF patients has been shown to provide complete remission in 64% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present findings, we think that as the quantity of real-life data increases, standard CAN protocols may be developed. Recently, a modified Delphi study suggested that in patients without any attacks or laboratory evidence of subclinical inflammation within 6 months of initiation of biologics the CAN dose interval can be doubled and in the absence of any new attacks within 1 year the dose interval can be tripled (5). Based on these suggestions, the same group of researchers are presently conducting a prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard definition for "colchicine resistance" in FMF patients. Clinicians agree that patients may be considered colchicine resistant in the presence of ongoing clinical disease activity and inflammation, whereas opinions vary regarding the frequency of attacks required to define patients as colchicine resistant (4,5). With the advent of translational research, anti-IL-1 agents have emerged as a new and effective therapeutic approach in colchicine-resistant FMF (crFMF) patients (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%